Pengaruh Merek, Kualitas Produk Dan Promosi Terhadap Keputusan Pembelian Produk Eiger (Studi Kasus Pada Generasi Z Di Kecamatan Lowokwaru) - Kurniawan, Hendri; Widarko, Agus; Saraswati, Ety (E-JRM : Elektronik Jurnal Riset Manajemen, 2025)
Abstract This study aims to analyze the influence of brand, product quality and promotion on purchasing decisions for Eiger products. The population used in this study is generation Z in Lowokwaru District who have purchased Eiger products. This type of research is quantitative research with a causal associative method. The sampling technique uses non-probability with the method used purposive sampling, the determination of the number of samples is obtained using the Hair et al. formula, so that 105 respondents are obtained. The analysis method used is multiple linear regression in the SPSS program. The results of this study indicate that brand, product quality and promotion have a positive and significant effect on purchasing decisions for Eiger products. This shows that if Eiger products improve and maintain the brand, product quality and promotion, the buyer's decision to purchase Eiger products will increase. Keywords: Brand, product quality, promotion, buying decision